Altered Pattern of Immunoglobulin A-Targeted Microbiota in Inflammatory Bowel Disease After Fecal Transplantation - Huang, Wen-qi; Huang, Hong-Li; Peng, Wu; Liu, Yan-Di; Zhou, You-Lian; Xu, Hao-Ming; Zhang, Liang-jie; Zhao, Chong; Nie, Yu-Qiang (Frontiers in Microbiology, 2022)
The adaptive immune response to the gut microbiota is one of the main drivers of inflammatory bowel disease (IBD). Immunoglobulin (Ig)-targeted bacteria are altered under inflammatory conditions. However, the changes in Ig-targeted bacteria in IBD Asian patients where has higher incidence of ulcerative colitis (UC) are still unclear. Furthermore, the changes in IgA-targeted bacteria in UC patients treated with FMT are also unclear. Here, we analyzed the fecal samples of IBD patients and UC patients pre/post-FMT by flow cytometry. We found that the percentage of IgA/G-coated bacteria can be used to assess the severity of IBD.In addition to oral pharyngeal bacteria such as Streptococcus species,as previous study showing,we also hypothesis that Megamonas ,Acinetobacters,especially Staphylococcus may play an important role in the pathogenesis of IBD. Furthermore, we evaluated the influence of FMT on IgA-coated bacteria in UC patients and found that IgA-bacterial interactions were re-established in human FMT recipients and resembled that of the healthy fecal donor. IgA-targeting was not influenced by the studied delivery methods: gastroscopy spraying and colonic transendoscopic enteral tubing (TET).Then we established the acute dextran sulfate sodium (DSS)-induced mice model to explore whether FMT intervention would impact the IgA/G memory B cell in the intestine .We found that after FMT,both the IgA/G memory B cell and the percentage of IgA/G targeted bacteria of the DSS mice has restored to normal level.